Strain rate effect on dislocation structure in dispersion-hardened alloy with incoherent nanoparticles - Daneyko, Olga I. (Russian physics journal)
The paper studies the influence of strain rate on the density of the dislocation system components in dispersionhardened materials having different scale parameters of the strengthening phase in a wide temperature range. According to mathematical simulation, the plastic shear rate of heterophased alloys with incoherent nanosized particles, affects the formation of dipole dislocation structures and, consequently, the material hardening. At high temperatures, the formation of dipoles does not occur in the dislocation structure of the material with the smallest particles at any strain rate. It is shown that during plastic strain, the density of shear dislocations is higher than that of dislocations in prismatic loops at all strain temperatures and rates in materials with strengthening particles of different size.